It doesn't factor any lower than that. I guess you could say (3*3)x.
x2+9x-36 = (x-3)(x+12) when factored
As written, -5x + 9x = 4x 4x - 4 = 4(x - 1) If that's -5x2 + 9x - 4, that factors to -(x - 1)(5x - 4)
If that's + 49y2, the answer is (9x - 7y)(9x - 7y) or (9x - 7y)2
If that's + 49y2, the answer is (9x - 7y)(9x - 7y) or (9x - 7y)2
If that's + 18x + 1, the answer is (9x + 1)(9x + 1) or (9x + 1)2
9x
x2+9x-36 = (x-3)(x+12) when factored
2x2 + 10 = 9x 2x2 - 9x + 10 = 0 (x - 2)(2x - 5) = 0
3x+21x+9x=33x. Break it apart. The factor of x is x and the factors of 33 are 3 and 11. Therefore, the factors of 3x+21x+9x are 3, 11, and x.
That factors to 4(9x + 5)
5x2 + 9x + 13 has no real factors.
82
You don't. This expression does not have any factors.
That factors to 3x(3x - 1)
As written, -5x + 9x = 4x 4x - 4 = 4(x - 1) If that's -5x2 + 9x - 4, that factors to -(x - 1)(5x - 4)
f(x) = x^2 - 9x - 10 = ( x - 10 ) ( x + 1 )Answer : ( x - 10 ) ( x + 1 )
-5x2+9x-4 -5x2+9x+-4 Factors of -20 that add to equal 9 are -5 and-4 -5x2+5x+4x+-4 -5x(1x+1) + 4x(1+-1x)